2013
DOI: 10.1504/ijass.2013.053347
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between governance, tie strength, and NPD performance

Abstract: This paper examines the impact of governance modes (norm of flexibility, trust, and monitoring) on NPD cycle time and the mediating role of relational ties strength. Our sample consists of 112 firms that were involved in NPD relationships. The results of structural equation modelling suggest that the trust and norm of flexibility are positively related to strength of relational ties while monitoring and strength of relational ties are not significantly related. On the other hand, relational ties strength is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 94 publications
1
5
0
Order By: Relevance
“…This study further confirmed that the strength of ties was influential to the performance in megaprojects. This was consistent with findings of the existing studies relating to strength of ties in other contexts (Bazyar et al , 2013; Gunawan et al , 2016; Lee and Yang, 2014; Teimoury et al , 2011). Additionally, the direct effect of weak ties on project performance was greater than the effect of strong ties.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study further confirmed that the strength of ties was influential to the performance in megaprojects. This was consistent with findings of the existing studies relating to strength of ties in other contexts (Bazyar et al , 2013; Gunawan et al , 2016; Lee and Yang, 2014; Teimoury et al , 2011). Additionally, the direct effect of weak ties on project performance was greater than the effect of strong ties.…”
Section: Discussionsupporting
confidence: 92%
“…The respondents’ basic information includes their designations, work experience and educational background. The strength of ties scale was designed based on prior studies (Bazyar et al , 2013; Collins and Clark, 2003; Levin and Cross, 2004). The scale of types of conflicts (Chen et al , 2014; Wu et al , 2017, 2018) and project performance (Castillo et al , 2017; Mesa et al , 2016; Nassar and Abourizk, 2014; Toor and Ogunlana, 2010) was also designed using the relevant literature.…”
Section: Methods and Data Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire items were further revised by five managers in the field of megaprojects. The strength of ties was adopted from Granovetter (1973), Hansen (1999) and Bazyar et al (2013). Term flexibility was assessed using the methods proposed by Cruz and Marques (2013) and Demirel et al (2017).…”
Section: Methods and Data Presentation Measurementsmentioning
confidence: 99%
“…In this study, variable measures were developed based on a systematic literature review and on-site interviews with experts. The measurement items of the strength of ties are drawn from the research of Granovetter (1973), Hansen (1999) and Bazyar et al (2013). The measurement items of trust derive from the research of McAllister (1995), Zaheer et al (1998), Pinto et al (2009) and Wu et al (2017).…”
Section: Methods and Data Presentationmentioning
confidence: 99%